Adapted sports and mental health: Promoting quality of life through lived experiences - Catunda, Felipe Nogueira; Ferreira, Heraldo Simões; Soares, Stela Lopes; Holanda, Sócrates Almeida (Nuances: estudos sobre Educação, 2023)
The study addresses the intersection of adapted sports, specifically adapted football for para-athletes, and mental health. The objective is to report the experience of physical education professionals in mental health for para-athletes, aiming to manage pre-competition anxiety effectively. The research adopts a qualitative approach through an experiential account within the context of descriptive research. The results revealed that adapted sports go beyond mere physical activity, taking on the role of an agent of social transformation and promoting the empowerment of individuals with disabilities. However, it was acknowledged that para-athletes face challenges, notably pre-competition anxiety, which can negatively impact their mental well-being. In light of this realization, mental health training emerges as a strategy to assist para-athletes in anxiety management, contributing to enhancing their performance. Additionally, it was observed that this training not only benefits individuals but can also positively impact teams as a whole.